Service quality and its relationship with customer satisfaction - How, Wong Eng; Sorooshian, Shahryar (Journal of Management and Science, 2013)
Nowadays, fast food restaurant grows very fast globally. This research is about study of customer satisfaction in the fast food restaurants. It aims to investigate the relationship between service quality and customer satisfaction. This study is using SERVPERF five dimensions to measure the level of service quality. By applying the service dimensions responsiveness, reliability and tangible in service quality, the level of customer satisfaction become higher. So, there is a positive correlation between service quality and customer satisfaction.